Nomotehnika, pravna država in politika - Grad, Franc (Pravni letopis, 2013)
The author discusses the relationship among the nomotechnics, the principle of legal state and the politics. He states that the nomotehnics belongs to the wider legal and social space, thus it depends especially on the legal and the political framework. The most important is the principle of legal state that represents the most important basis for the creating of law. From the aspect of legal framework it is necessary that the legal order should be coherent, thus the nomotechnics finding its firm basis for its work. The legal environment includes especially the constitutional framework and the European law framework of the working of nomotehnics.The political environment means the regulated political functioning that realises the political aims with concerning the legal rules.
Keywords: nomotehnika; politics; politika; pravna država; ustavnost; zakonodaja; zakonodajni postopek